Comparative Exceptionalism: Universality and Particularity in Foreign Policy Discourses. Issue 1 (22nd March 2018) - Nymalm, Nicola; Plagemann, Johannes
Abstract: Existing research on exceptionalism in foreign policy suggests a number of confrontational features making it a threat to peaceful international relations. Largely based on US and European cases, and hardly ever taking a comparative approach, this literature overlooks a variety of exceptionalisms in non-Western countries, including so called "rising powers" such as China and India. A comparison between exceptionalist foreign policy discourses of the United States, China, India, and Turkey shows that exceptionalism is neither exclusive to the United States, nor a "new" phenomenon within rising powers, nor necessarily confrontational, unilateralist, or exemptionalist. As a prerequisite for comparative work, we establish two features common to all exceptionalist foreign policy discourses. In essence, such discourses are informed by supposedly universal values derived from a particular civilization heritage or political history. In order to systematize different versions of exceptionalism, we then propose four ideal types, each of which reflects exceptionalism's common trait of a claim to moral superiority and uniqueness but diverges across other important dimensions, with implications for its potentially offensive character. The article concludes by formulating a research agenda for future comparative work on exceptionalist foreign policy discourses and their repercussions for great power relations and global politics.